The economic significance of the development of ecological tourism. - Otajonov Sh.E.; Otajonova S.R. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The economic system plays an important role in the development of the ecological system. Especially Western countries pay special attention to the ecotourism system, because ecotourism is a promising and profitable type.